(untitled) (Annals of Medical Research, 2024)
Pancreaticoduodenectomy is one of the major gastrointestinal surgeries and still has significant complication rates. Although most complications appear postoperatively, severe intraoperative difficulties and complications can occur in certain circumstances. Here, we presented the management of two cases who underwent two-stage pancreaticoduodenectomy due to intraoperative problems. Two patients have become hemodynamically unstable during an elective pancreatic resection combined with both arterial and venous reconstructions. All the gastrointestinal reconstructions were postponed to second sessions for damage control surgery. A two-stage pancreaticoduodenectomy is an option to be considered in a hemodynamically unstable patient during elective pancreaticoduodenectomy.